Tolerance of Venerupis philippinarum to salinity: Osmotic and metabolic aspects - Carregosa, Vanessa
In the last few decades, attention has been focused on the impacts of contamination in marine benthic populations, while the responses of aquatic organisms to natural alterations, namely changes in salinity, have received little attention. In fact, salinity is one of the dominant environmental factors affecting marine bivalves. The ebb and flood of the tide, combined with fresh water inputs from rivers or heavy rainy events, and with extremely dry and hot seasons, can dramatically alter water salinity. Therefore, the salinity of a certain environment can restrict the spatial distribution of a given population, which is especially important when assessing the spread of an invasive species into a new environment. In the present study, the main objective was to understand how clam Venerupis philippinarum copes with salinity changes and, hence biochemical and metabolomic alterations, taking place in individuals submitted to a wide range of salinities were investigated. The results showed that V. philippinarum presented high mortality at lower salinities (0 and 7 g/L) but tolerated high salinities (35 and 42 g/L). The quantification of ionic content revealed that, clams had the capacity to maintain ionic homeostasis along the salinity gradient, mainly changing the concentration of Na, but also with the influence of Mg and Ca. The results showed a decrease in protein content at lower salinities (0 to 21 g/L). Glycogen and glucose increased with increasing salinity gradient. H-1 Nuclear Magnetic Resonance (NMR) spectra of clam aqueous extracts revealed different metabolite profiles at 7, 28 and 42 g/L salinities, thus enabling metabolite changes to be measured in relation to salinity. (C) 2014 Elsevier Inc All rights reserved.